Meningococcal vaccines. - Rüggeberg, J; Pollard, A (2004)
Meningococcal disease is one of the most feared and serious infections in the young and its prevention by vaccination is an important goal. The high degree of antigenic variability of the organism makes the meningococcus a challenging target for vaccine prevention. Meningococcal polysaccharide vaccines against serogroup A and C are efficacious and have been widely used, often in combination with serogroup Y and W135 components. Their relative lack of immunogenicity in young children and infants can be overcome by conjugation to a protein carrier. The effectiveness of serogroup C glycoconjugate vaccines in children of all ages has been demonstrated and they have now been introduced into routine vaccination schedules. Conjugate vaccines against other serogroups, including A, Y, and W135 will soon be available and it is hoped they may emulate this success. Prevention of serogroup B disease has proven more elusive. Several serogroup B vaccines based on outer membrane vesicles have been shown to be immunogenic and reasonably effective in adults and older children, but the protection offered by them is chiefly strain-specific. Multivalent recombinant PorA vaccines have been developed to broaden the protective effect, but no efficacy data are available as yet. Intensive efforts have been directed at other outer membrane protein vaccine candidates and lipopolysaccharide, and some of these have been shown to offer protection in experimental animal models. Nonpathogenic Neisseriae spp. such as Neisseria lactamica are also possible vaccine candidates. Previously unknown proteins have been identified from in silico analysis of the meningococcal genome and their vaccine potential explored. However, none of these has yet been presented as the 'universal' protective antigen and work in this field continues to be held back by our limited knowledge concerning the mechanisms of natural protection against serogroup B meningococci.